An Analysis of Caste Discrimination and Untouchability in R.B. Nischal's Poem Paitālā Pukār 2 - Magarati, Shyam Lal (Journal of NELTA Karnali, 2022)
This paper examines the socio-cultural issues of Dalits. The objective of the study was to analyze caste discrimination and untouchability of Dalits. For this objective, the researcher has employed Stuart Hall's theoretical insights of representation under cultural studies. The poem was selected purposively and it was the library based qualitative research. The data were collected from record-keeping and description. The researcher found that Dalit community that has suffered from the time immemorial in every aspect due to generational, multi-faceted and institutionalized discrimination due to the Hindu caste system in Nepal for religious and political reasons. This unfair practice has left a clear mark of social division, exclusion and inequality which has severely ruined Dalits' life and identity. Addressing this issue in the poem Paital Puk r Ram Bahadur Kami, displays episodes of verbal and physical violence and recurrent intra-caste discrimination. As well as he depicts the traumatic existence of the Dalit oppressed community. Other dominations and discriminations are less traumatic in comparison of cultural trauma which is like an incurable disease. Therefore, this paper displays how the Dalit people have been living in a society bearing harsh torture, trauma and inhuman treatment. Moreover, it is significant for academia for representing diverse cultural experiences and people and it can be a valuable asset for the society.